(untitled) - Wang, Joseph (Weinheim, 2013)
Nanomachines represent one of the most fascinating topics in of nanotechnology. These tiny devices provide diverse opportunities towards a wide range of important applications, ranging from targeted delivery of drug payloads to environmental remediation. This book addresses comprehensively the latest developments and discoveries in the field of nano- and microscale machines. It covers the evolution of nanomachines in general from a historical perspective, the fundamental challenges for motion at the nanoscale, different categories of biological and synthetic nano/microscale motors based on different propulsion mechanisms, ways for controlling the movement directionality and regulated speed, followed by detailed of major areas for which nanomachines has the potential to make a transformational impact. It ends with a futuristic look at nano/microscale machines and into their impact on the society.
Keywords: Nanoelectromechanical systems,Hệ thống cơ điện nano